1987
DOI: 10.1021/bi00384a027
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of reduction by free flavin semiquinones of the components of the cytochrome c-cytochrome c peroxidase complex and intracomplex electron transfer

Abstract: The kinetics of reduction by free flavin semiquinones of the individual components of 1:1 complexes of yeast ferric and ferryl cytochrome c peroxidase and the cytochromes c of horse, tuna, and yeast (iso-2) have been studied. Complex formation decreases the rate constant for reduction of ferric peroxidase by 44%. On the basis of a computer model of the complex structure [Poulos, T.L., & Finzel, B.C. (1984) Pept. Protein Rev. 4, 115-171], this decrease cannot be accounted for by steric effects and suggests a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
101
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(109 citation statements)
references
References 64 publications
7
101
1
Order By: Relevance
“…We have found that, in each case, on NOE connectivity to phenyl ring protons of Phe82 near 6.0ppm is observed upon irradiation of the heme 3-CH3 resonance (Satterlee and Moench, 1987;Moench and Satterlee, 1989). In contrast, two-dimensional (2 D) NOESY experiments are less useful in this respect (Busseet al, 1990).…”
Section: Probing the Phe82 Environment Of Cytochrome C By Proton N M Rmentioning
confidence: 85%
See 4 more Smart Citations
“…We have found that, in each case, on NOE connectivity to phenyl ring protons of Phe82 near 6.0ppm is observed upon irradiation of the heme 3-CH3 resonance (Satterlee and Moench, 1987;Moench and Satterlee, 1989). In contrast, two-dimensional (2 D) NOESY experiments are less useful in this respect (Busseet al, 1990).…”
Section: Probing the Phe82 Environment Of Cytochrome C By Proton N M Rmentioning
confidence: 85%
“…pH values are reported as 'p2H' which is the pH meter reading uncorrected for the deuterium effect. Singlepulse and pre-steady-state one-dimensional (1 D) NOE measurements were carried out as previously described (Satterlee and Moench, 1987). Irradiation pulse durations for data acquistions were generally 100 ms and decoupler power levels used for irradiation were 200 mW or less.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations